Mobile-Based Interactive Multimedia Learning for Problem-Solving Skills in Vocational High School - Aurum, Emma Valensia; Surjono, Herman Dwi (Jurnal Pendidikan Indonesia, 2021)
This research aims to solve some common problems faced by learners, namely difficulties in understanding materials with abstract ideas and the lack of problem-solving skills. Mobile-based interactive learning multimedia as an innovation in educational setting is a self-learning media that the learners can use both in school and at home to help them understand the materials easily, minimize learning difficulties, and increase their problem-solving skills. This is a Research and Development (R&D) with the APPED model. The subjects of this research were the 10th grade students of the Vocational Program of Computer and Network Technology at SMK Negeri 1 Tulung Klaten (State Vocational School 1 of Tulung, Klaten). The data analysis technique was done through the descriptive quantitative. The results showed that the mobile-based interactive multimedia learning was feasible with the Very Good category. The mobile-learning-based interactive multimedia learning was effectively used with a percentage of 77.85% and the difference in significance, based on the Wilcoxon Test on the pretest posttest of 0.000 it indicates that there is a difference in the increase in problem-solving skills while learning using the mobile-based interactive multimedia learning.